Staff perceptions of positive behavioural support in a secure forensic adult mental health setting. Issue 1 (18th January 2018) - Karger, Graeme; Davies, Bronwen; Jenkins, Rosemary; Samuel, Victoria
Abstract : Purpose: Challenging behaviour has been a concern across forensic services. Traditionally these have been managed reactively using medication, seclusion and restraint; however, there is growing evidence that these approaches are ineffective and counter-therapeutic. A number of reports have recommended the use of preventative approaches such as positive behavioural support (PBS). The purpose of this paper is to identify "how staff within a secure forensic mental health setting perceived the application of PBS?" Design/methodology/approach: In total, 11 multi-disciplinary staff were interviewed and thematic analysis was used to identify themes. Findings: Five themes were identified: "The Functions", "Appraising a new Approach", "Collaborative Challenges", "Staff Variables" and "Organisational Issues". Practical implications: PBS enables staff to understand challenging or risky behaviour. It empowers patients via collaboration, although there can be some challenges to this. Services need to invest in training, support and leadership to ensure the model is embed and promote fidelity. Consideration needs to be given to how quality of life can be improved within the limits of a forensic setting. Originality/value: No previous studies asking staff about their experiences of PBS within a forensic mental health context.